Cognitive Appraisals Affect Both Embodiment of Thermal Sensation and Its Mapping to Thermal Evaluation - Keeling, Trevor P.; Roesch, Etienne B.; Clements-Croome, Derek (Frontiers in Psychology, 2016)
The physical environment leads to a thermal sensation, which perceived and appraised by occupants. The present study focusses on the relationship between sensation and evaluation. We asked 166 people to recall a thermal event from their recent past. They were then asked how they evaluated this experience in terms of ten different emotions (frustrated, resigned, dislike, indifferent, angry, anxious, liking, joyful, regretful, proud). We tested whether four psychological factors (appraisal dimensions) could be used to predict the ensuing emotions, comfort, acceptability and sensation. The four dimensions were: the Conduciveness of the event, who/what caused the event (Causality), who had control (Agency) and whether the event was expected (Expectations). These dimensions, except for Expectations, were good predictors of the reported emotions. Expectations, however, predicted the reported thermal sensation, its acceptability and ensuing comfort. The more expected an event was, the more uncomfortable a person felt, and the less likely they reported a neutral thermal sensation. Together, these results suggest support an embodied view of how subjective appraisals affect thermal experience. Overall, we show that appraisal dimensions mediate occupants’ evaluation of their thermal sensation, which suggests an additional method for understanding psychological adaption.